Intensive Rehabilitation Enhances Lymphocyte BDNF-TrkB Signaling in Patients With Parkinson's Disease. (June 2016) - Fontanesi, Cecilia; Kvint, Svetlana; Frazzitta, Giuseppe; Bera, Rossana; Ferrazzoli, Davide; Di Rocco, Alessandro; Rebholz, Heike; Friedman, Eitan; Pezzoli, Gianni; Quartarone, Angelo; Wang, Hoau-Yan; Ghilardi, M. Felice
Background . In a combined animal and human study, we have previously found that a 5-day treatment that enhances cortical plasticity also facilitates brain-derived neurotrophic factor (BDNF)-tyrosine receptor kinase B (TrkB) signaling and increases activated TrkB and N -methyl-d -aspartate receptor (NMDAR) association in both the cortex and the peripheral lymphocytes. Patients with Parkinson's disease (PD), in general, show decreased cortical plasticity, as demonstrated by electrophysiological and behavioral studies. Here, we test the hypothesis that an exercise program that improves motor function and seems to slow down symptom progression can enhance BDNF-TrkB signaling in lymphocytes. Methods . A total of 16 patients with PD underwent a 4-week multidisciplinary intensive rehabilitation treatment (MIRT), which included aerobic training and physical and occupational therapy. Blood was collected before and after 2 and 4 weeks of MIRT. Lymphocytes were isolated to examine BDNF-TrkB signaling induced by incubation with recombinant human BDNF. TrkB signaling complexes, extracellular-signal-regulated kinase-2 and protein-kinase-B were immunoprecipitated; the content of immunocomplexes was determined by Western blotting. Results . After MIRT, all patients showed improvement in motor function. TrkB interaction with NMDAR and BDNF-TrkB signaling increased in peripheral lymphocytes at receptor, intracellular mediator, and downstream levels. The decrements in Unified Parkinson's Disease Rating Scale II (UPDRSII) and total scores were significantly correlated with the increases in TrkB signaling at receptor, intracellular mediator, and NMDAR interaction levels. Conclusions . The significant correlation between reduced UPDRS scores and the changes in lymphocyte activity suggest that enhanced BDNF-TrkB signaling in lymphocyte and reduced severity of PD symptoms may be related.